Hambatan Program Human Resources Development Indonesia- Malaysia-Thailand Growth Triangle dalam Mengurangi Kemiskinan di Aceh - Windiani, Reni; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research aims to explain the obstacles of HRD program by IMT-GT in reducing thepoverty in Aceh. Various effort had been made to reduce poverty in Aceh. One of them wasthe IMT-GT (Indonesia-Malaysia-Thailand Growth Triangle) as a sub-regionalcooperation. However, through the HRD (Human Resources Development) program aimsto reduce poverty and improve the quality of life, is not effective either. This research usedqualitative methods, with neo-functionalism theory to prove the hypothesis. The result ofthis research found out that the ineffectiveness of IMT-GT HRD program was caused bythe failure of IMT-GT to create good regional integration and the failure of HRD to workon spillover scheme.